1997
DOI: 10.1007/pl00003406
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics of lumbar instability

Abstract: Several authors have tried to define segmental lumbar instability. Their definitions: increased antero-posterior translation, pathologic coupled motion, increased neutral zone, pathologic instantaneous center of rotation describe some mechanic findings occurring in the aging spine. However, there is no evidence that they help to differentiate the pathologic entity of segmental lumbar instability from the normal aging process. Dynamic explanation models are promising but at the moment they cannot be used clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Changes in SMS mechanical function with mild disk degeneration have been explored both ex vivo and in silico. Ex vivo, some studies confirmed the hypothesis,111213 whereas others, including a comprehensive study with over 200 cadaveric motion segments, demonstrated the opposite (i.e., decreasing range of motion and/or increasing stiffness) 1415. Using a phenomenological finite element (FE) approach, the main characteristics of disk degeneration and their severity were combined to build a variety of motion segment models 16.…”
Section: Indirect Painmentioning
confidence: 95%
“…Changes in SMS mechanical function with mild disk degeneration have been explored both ex vivo and in silico. Ex vivo, some studies confirmed the hypothesis,111213 whereas others, including a comprehensive study with over 200 cadaveric motion segments, demonstrated the opposite (i.e., decreasing range of motion and/or increasing stiffness) 1415. Using a phenomenological finite element (FE) approach, the main characteristics of disk degeneration and their severity were combined to build a variety of motion segment models 16.…”
Section: Indirect Painmentioning
confidence: 95%
“…The degenerative process in the disk results in a gradual disruption of the collagen fibers and reduction in the proteoglycan contents, with a gradual loss of water contents and elasticity of the disk (35). More than 50% of autopsy specimens obtained from individuals in their 3rd and 4th decade of life show peripheral tears of the annulus fibrosus (36). After age 40 years, the disk becomes progressively more fibrous and disorganized due to aging and degeneration; the final stage is represented by regions of amorphous fibrocartilage (37).…”
Section: Degenerative Lumbar Intervertebral Instabilitymentioning
confidence: 99%
“…Although these abnormalities may be related to each other, and gradually overlap the physiological ageing course [12], in most of the literature they are described and defined as degenerative disc disease [4,76] and are, therefore, clearly distinct from natural ageing. An analysis of midsagittal sections of cadaveric specimens showed that more than 50 % of intervertebral discs in the third and fourth decade of life exhibit annular tears and fissures [40]. Tears were shown to have different orientations and extents and are classified following the terminology shown in Fig.…”
Section: Structural Changesmentioning
confidence: 99%